When employees and external consultants work together on projects: Challenges of knowledge sharing. Issue 7 (October 2015) - Nesheim, Torstein; Hunskaar, Håavard Mørch
Abstract In project settings, personnel with different employment arrangements often work together and interact closely. Here, we study knowledge sharing when employees of the focal firm cooperate with external consultants. We differentiate between "in-group" (inside an employment category) and "out-group" (between employment categories) knowledge sharing and analyze the antecedents of knowledge sharing behavior. In an empirical study of 117 employees and external consultants, we find strong support for the main hypotheses: Internal employees tend to engage in more knowledge sharing than external consultants, in their relation to employees. Employees tend to engage in less knowledge sharing than external consultants, in their relation to external consultants. Trust in relation to a specific category of employment was also found to be statistically related to knowledge sharing behavior toward personnel in the category.